Social Media Marketing Pada PT BNI Persero Cabang Palembang - M. Audy Zidan; Neneng Miskiyah; Hendra Sastrawinata (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study explains the existence of social media Instagram at PT BNI Persero Cabang Dempo Palembang to find out the extent of social media influence on customer loyalty. This study uses primary data in the form of results from answers to questionnaires. This study uses a quantitative method with multiple linear regression analysis with the results showing that the convenience variable obtained the t value of 4.921 with a significance value of 0.000 less than 0.05. The trust variable obtained by t count value of 4.289 with a significance value of 0.000, less than 0.05. Overall, based on the results of the research and the results of the analysis that has been done, the ease and trust of social media together have a positive and significant effect on customer loyalty at BNI Cabang Dempo Palembang.